O grotesco midiático: estratégias de imagem nas charges de imprensa. - Miranda, Vivian Castro de (2009)
This dissertation analysis has as theme the grotesque media. In such way, the general objective seeks to understand the grotesque through the humor cartoons in the printed media journalism. The justification for such research is the possibility to understand better the phenomenon through the gear of the humorous texts. For this, parting from a semiological approach, some specific objectives were proposed: (i) understand the expressive manners that the grotesque assumes in the press media, which represent certain modes of discursiveness; (ii) explicit the senses constructed in the humorous text, specially the grotesque, once the comical aspect appeals to it and (iii) point out the discursive strategies used for the construction of senses, that is, the constructions in terms of language (visual, verbal) that operate while textual strategies are demonstrated, above all, through images. We wish to demonstrate that the grotesque is a signification that operates as a start for the comical aspect in the newspapers. Some of the conclusions which can be pointed out are: the existence of an interface information/amusement, once the meaning of the charges are related to or extend the meaning of the news, the relevance of the visual component of the expression in terms of the construction of the senses in these texts and the demonstration of different discursive strategies in what refers to the enunciation of the journalistic humor.